LITERASI KEUANGAN, GAYA HIDUP, LOCUS OF CONTROL, DAN PARENTAL INCOME TERHADAP PERILAKU KEUANGAN MAHASISWA - Nuraeni Ritakumalasari; Ari Susanti (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2021)
A financial attitude is essential for all young people, especially students, to avoid strange financial problems. Especially in this pandemic period, it must be good at managing its finances appropriately so as not to experience waste. This study explains financial literacy, lifestyle, locus of control, and parental income on student financial behaviour in Central Java. The population in this study are students of Central Java province, which numbered 400 respondents with the formula Slovin. Purposive sampling technique determining sample criteria. This research uses quantitative data obtained from a questionnaire google form. Data were analyzed through multiple regression analysis with IBM SPSS Statistics 25. The results explain that financial literacy, lifestyle, locus of control, and parental income significantly influence student financial behaviour in Central Java province. Universities must continue to encourage students to manage their finances, and students need to realize the importance of understanding financial behaviour in their lives. The beginning can be started by allocating money in the form of investment, insurance, savings, investment, and others to feel the benefits in the future.